Research for Promoting Sustainable Farming Systems in arid and semi-arid areas of Morocco: Challenges, achievements and future prospects - Moussadek, Rachid; Ouabbou, Hassan; El Gharras, Oussama; Dahan, Rachid; El Mourid, Mohamad (National Institute of Agronomic Research Morocco, 2024)
This book introduces research axis results that aim conserving natural resources, improving the efficiency of resource use, and research schemes to developing crop varieties that can improve productivity by increasing yield, reducing the crop cycle to mature, increasing tolerance to stresses such as drought, salinity, pests, and disease, and improving technological quality of crops, in all, solutions on the ground that farmers can adopt to enhance positive effects towards greater adaptive capacity.